The Use of Wastewater in the Irrigation of Agricultural Soils and its Contamination Effect by Trace Elements: A Review - Kerboua Faycal (European Scientific Journal, ESJ, 2018)
Wastewater reuse (either raw or treated) for irrigation of crops is a common widespread practice around the world. This water provides the soil with many nutrient elements. However, it also results to organic and metallic contaminants. This may have a significant effect on the physico-chemical characteristics of the soil and the crops contamination. It is a fact that constitutes a huge risk which is both sanitary and environmental. This paper focuses on explaining the effect of the use of wastewater in the irrigation of the agricultural soils and crops and their contamination by trace elements.